A carbon-nitrogen-doped mesoporous silica supported copper-based catalyst for ester hydrogenation and methods of making and using the same
By loading a carbon-nitrogen-doped copper-based catalyst onto a mesoporous silica support and utilizing the coordination effect of pyrrole nitrogen with copper, the problem of high pressure and high temperature in the hydrogenation reaction of oxalate esters was solved, and the efficient preparation of ethylene glycol under low temperature and low pressure was achieved, which has good prospects for industrial application.
Patent Information
- Application Number
- CN202410161628.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-05
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-02-05
AI Technical Summary
Existing technologies for the hydrogenation of oxalate esters to ethylene glycol involve high reaction pressures and temperatures, resulting in demanding equipment requirements, poor catalyst thermal stability, and high energy costs.
A copper-based catalyst is supported on a carbon-nitrogen-doped mesoporous silica support. Through the coordination and anchoring of pyrrole nitrogen with copper species, the dispersion and electronic valence of copper species are improved, promoting the adsorption and activation of reactant molecules, thus achieving a highly selective hydrogenation reaction at low temperature and low pressure.
Achieving high selectivity conversion of oxalate and 98.5% selectivity of ethylene glycol at low temperature (170℃) and low pressure (0.5MPa) reduces equipment costs and energy consumption. Meanwhile, the catalyst preparation raw materials are readily available and low in cost, and the synthesis process is simple and controllable.
Smart Images

Figure CN118106009B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas-phase ester hydrogenation catalyst technology, and relates to a catalyst for loading copper on a carbon-nitrogen-doped mesoporous silica support, particularly a copper-based catalyst for ester hydrogenation supported on carbon-nitrogen-doped mesoporous silica, and its preparation and application methods. Background Technology
[0002] Ethylene glycol (EG) is an important chemical raw material or solvent, widely used in the production of polyester and its downstream products, antifreeze, lubricants, etc. In existing technologies, the process of producing dimethyl oxalate via carbon monoxide coupling from syngas, followed by hydrogenation of dimethyl oxalate to ethylene glycol, features high atom economy, mild reaction conditions, high product selectivity, and environmental friendliness. This process is one of the important non-petroleum routes for synthesizing ethylene glycol, with the hydrogenation of dimethyl oxalate to ethylene glycol being the core step.
[0003] Copper-based catalysts exhibit good activity and selectivity in this reaction system due to their excellent hydrogenation performance; however, the high pressure and temperature required for the reaction remain unresolved. Currently, the hydrogenation reaction of dimethyl oxalate (DMO) typically requires a pressure of 2.5 MPa and a reaction temperature of 200 °C or higher, under which these conditions can achieve high activity and ethylene glycol yield. However, in industrial applications, excessively high pressures place more stringent demands on the reaction equipment. Furthermore, excessively high reaction temperatures can cause copper particles to agglomerate and sinter, leading to poor catalyst thermal stability, while also increasing energy consumption costs. Therefore, designing novel, highly active copper-based catalysts that enable high ethylene glycol yields in the hydrogenation reaction of oxalate esters under low pressure and low temperature is crucial for optimizing the syngas-to-ethylene glycol process. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and address the problem of high reaction pressure and temperature in the hydrogenation of oxalate to ethylene glycol. This invention proposes a copper-based catalyst supported on a carbon-nitrogen-doped mesoporous silica support and applies it to the oxalate hydrogenation system. The carbon and nitrogen are highly dispersed within the mesoporous silica channels. The coordination and anchoring effect of pyrrole nitrogen on copper species enhances the dispersion of copper species on the catalyst surface and regulates the interaction between copper and the support, thereby altering their electronic valence states and distribution ratios. This promotes the adsorption and activation of reactant molecules by the catalyst, achieving highly selective oxalate to ethylene glycol production under low temperature and low pressure.
[0005] This invention is achieved through the following technical solution:
[0006] The copper-based catalyst supported on a carbon-nitrogen-doped mesoporous silica support for oxalate hydrogenation in this invention has the following main chemical components: copper, carbon, nitrogen, and silica. Copper accounts for 2-30 wt.% of the catalyst mass, carbon accounts for 0.1-10 wt.%, nitrogen accounts for 0.1-5 wt.%, and silica accounts for 55-97.8 wt.%. A preferred embodiment is: copper accounts for 5-15 wt.%, carbon accounts for 0.5-5 wt.%, nitrogen accounts for 0.5-2 wt.%, and silica accounts for 78-94 wt.%.
[0007] The catalyst is a mesoporous silica-supported catalyst with a specific surface area of 400-600 m². 2 / g, with an average pore volume of 0.5-1.5cm³. 3 / g, with an average pore size of 4-7nm; the preferred option is a catalyst with a specific surface area of 450-500m². 2 / g, with an average pore volume of 0.7-1.0 cm³. 3 / g, with an average pore size of 5.5-6.0nm.
[0008] Another object of the present invention is to provide a method for preparing a copper-based catalyst supported on a carbon-nitrogen-doped mesoporous silica support for oxalate hydrogenation, comprising the following steps:
[0009] (1) The template agent polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) was completely dissolved in an acidic aqueous solution, and the temperature was maintained at 25-50℃ while stirring for 5-20 hours to obtain a clear solution. A silicon source was then added to the above clear solution, and the temperature was maintained at 25-50℃ while stirring for 10-40 hours. The resulting product was transferred to an autoclave and subjected to hydrothermal crystallization treatment at 60-150℃, followed by standing for 10-40 hours.
[0010] The acidic aqueous solution is any one of hydrochloric acid, sulfuric acid, or nitric acid aqueous solution, and the silicon source is any one of sodium silicate, silica sol, or tetraethyl orthosilicate.
[0011] (2) The product from step (1) is washed with deionized water until neutral. The washed product is dried at 40-100℃ for 5-15 hours. Then it is calcined at 400-700℃ in air for 2-10 hours to remove the template agent and obtain silicon oxide with a uniform mesoporous structure.
[0012] The washing method is either filtration washing or centrifugal washing, and the drying method is either ordinary drying method or vacuum drying method.
[0013] (3) The mesoporous silica product from step (2) is added to deionized water and sonicated. Then, carbon-nitrogen precursors of different masses are added, maintaining a mass ratio of carbon-nitrogen precursors to mesoporous silica of 0.2-1.5. The mixture is stirred at 25-50℃ for 15-25 hours and then separated by rotary evaporation. The resulting product is dried at 40-100℃ for 5-15 hours and then calcined at 400-800℃ for 2-10 hours under a nitrogen atmosphere to obtain a carbon-nitrogen-doped mesoporous silica support.
[0014] The carbon-nitrogen precursor is any one of melamine, dimelamine, or urea, and the drying method is either a conventional drying method or a vacuum drying method.
[0015] (4) Dissolve the copper salt precursor in an aqueous solution, add the product from step (3), and maintain the temperature at 25-50℃. Stir for 5-15 hours and then perform rotary evaporation to separate the water and solid product. Dry the obtained product at 40-100℃ for 5-15 hours, and then calcine it at 300-500℃ for 2-5 hours under a nitrogen atmosphere to obtain a copper-based catalyst supported on a carbon-nitrogen-doped mesoporous silica support.
[0016] The copper salt precursor is any one of copper acetate, copper sulfate, copper chloride, and copper nitrate.
[0017] A more preferred embodiment of the above scheme is: the acidic aqueous solution in step (1) is hydrochloric acid aqueous solution. The silicon source of the silicon oxide is tetraethyl orthosilicate. The washing method is filtration washing. The drying method is vacuum drying. The carbon-nitrogen precursor is urea. The copper precursor salt solution is copper nitrate.
[0018] In step 2, the carbon and nitrogen content can be adjusted by changing the ratio of the carbon-nitrogen precursor to mesoporous silica. The nitrogen species is preferably pyrrole nitrogen, and copper is used to coordinate and anchor the nitrogen species to form a Cu-N species. The mass ratio of the carbon-nitrogen precursor to mesoporous silica used to form pyrrole nitrogen is between 0.5 and 1.0.
[0019] The catalyst needs to be reduced online before use. Specifically, the reduction temperature is 150-400℃, the reduction atmosphere is hydrogen, and the hydrogen flow rate required for the reduction of each gram of catalyst is 20-100 mL / min.
[0020] The catalyst is used in the following manner: in the hydrogenation reaction of oxalate ester, the reaction pressure is 0.1-3.0 MPa, the reaction temperature is 150-220℃, the hydrogen-to-ester ratio is 50-150, and the liquid hourly space velocity is 0.05-1.0 h⁻¹. -1 The liquid hourly space velocity (LISH) refers to the LISH of oxalate ester.
[0021] The advantages and positive effects of this invention are:
[0022] 1. The catalyst developed in this invention is applied to the hydrogenation of oxalate to ethylene glycol reaction. It exhibits excellent catalytic activity (100% oxalate conversion and 98.5% ethylene glycol selectivity) under low temperature (170°C) and low pressure (0.5 MPa) conditions. In industry, it can greatly reduce the requirements for equipment, thereby reducing equipment costs, and at the same time, it can significantly reduce reaction energy consumption.
[0023] 2. This invention allows for flexible adjustment of the carbon and nitrogen content and the types of nitrogen species by changing the mass ratio of carbon and nitrogen precursors to mesoporous silica. It was discovered that copper species coordinate with pyrrole nitrogen to form Cu-N species, which then anchors the copper species and improves their dispersion. Furthermore, due to the formation of Cu-N species, the copper species transfers electrons to nitrogen, which modulates the electronic valence state of the copper species, placing it in a more electron-deficient state. This results in stronger adsorption and activation capabilities for reactant molecules, thereby achieving efficient hydrogenation of oxalate esters to ethylene glycol under low temperature and low pressure.
[0024] 3. The catalyst developed in this invention has the advantages of readily available raw materials, low cost, simple and controllable synthesis process, strong operability, and good industrial application prospects. Attached Figure Description
[0025] Figure 1 Thermogravimetric analysis (TGA) diagrams of copper-based catalysts supported on ordered mesoporous silica with different carbon and nitrogen doping contents according to the present invention.
[0026] Figure 2 The accompanying diagram shows the N2 isothermal adsorption-desorption of copper-based catalysts supported on ordered mesoporous silica with different carbon and nitrogen doping contents according to the present invention.
[0027] Figure 3 The X-ray diffraction (XRD) patterns of copper-based catalysts supported on mesoporous silica with different carbon and nitrogen doping contents after reduction according to the present invention.
[0028] Figure 4 The image shows a transmission electron microscope (TEM) image of the catalyst of the present invention and a corresponding particle size distribution.
[0029] Figure 5 This is the X-ray photoelectron spectroscopy (XPS) spectrum of the catalyst of the present invention with respect to Cu.
[0030] Figure 6 This is the X-ray photoelectron spectroscopy (XPS) spectrum of the catalyst of this invention with respect to nitrogen.
[0031] Figure 7 The temperature-programmed desorption mass spectrometry (MG-TPD-MS) of methyl glycolate for the catalyst of this invention is shown. Detailed Implementation
[0032] The present invention will be further described below through embodiments, but is not limited to these embodiments. Experimental methods not specifically described in the embodiments generally use conventional conditions and conditions described in the manual, or conditions recommended by the manufacturer. The general equipment, materials, reagents, etc., used are all commercially available unless otherwise specified.
[0033] Example 1
[0034] Preparation of mesoporous silica materials:
[0035] Weigh 4g of the template agent poly(ethylene oxide-poly(propylene oxide-poly(ethylene oxide)) (P123) and add it to 120mL of 2M HCl aqueous solution. Stir at 40℃ for 12h until completely dissolved to obtain a clear solution A. Add 8.5g of tetraethyl orthosilicate dropwise to solution A at a uniform rate and stir at 40℃ for 24h to obtain solution B. Place solution B in a sealed container and hydrothermally treat at 100℃ for 24h. Filter and wash the obtained product with deionized water until neutral, dry at 60℃ for 10h, and calcine at 550℃ for 6h in air to obtain a uniform mesoporous silica material.
[0036] Preparation of carbon and nitrogen-doped mesoporous silica supports:
[0037] 1g of mesoporous silica was added to 100mL of deionized water, sonicated for 10min, and then 0.8g of urea was added. The mixture was stirred at 30℃ for 20h, and the water was removed by rotary evaporation. The solid product was then placed in a vacuum oven at 70℃ for 10h and calcined at 550℃ under a nitrogen atmosphere for 2h to obtain a carbon-nitrogen-doped mesoporous silica support.
[0038] Catalyst preparation:
[0039] 0.4 g of copper nitrate trihydrate was dissolved in an appropriate amount of deionized water to obtain a clear solution. A carbon-nitrogen-doped mesoporous silica support was added, and the mixture was stirred at 30 °C for 10 h. The water was removed by rotary evaporation, and the solid product was then placed in a vacuum oven at 70 °C for 10 h and calcined at 400 °C under a nitrogen atmosphere for 2 h to obtain the catalyst.
[0040] Catalyst evaluation:
[0041] In this invention, the gas-phase hydrogenation reaction of oxalate is carried out in a fixed-bed reactor. The calcined catalyst is pressed into tablets and sieved to a size of 40-60 mesh. 0.5 g of catalyst is loaded and reduced at 250 °C in a 0.5 MPa H₂ atmosphere with a gas flow rate of 40 mL / min. The temperature is increased from room temperature to 250 °C at a rate of 2 °C / min and maintained for 3 h. The temperature is then lowered to the reaction temperature of 170 °C, and the oxalate is vaporized and mixed with hydrogen before entering the reaction tube. The hydrogen-to-ester ratio is 100, and the oxalate mass hourly space velocity (WHSV) is 0.2 h⁻¹. -1 The reaction was carried out at 0.5 MPa. The products were analyzed by gas chromatography, and the catalyst evaluation results are shown in Table 1.
[0042] Comparative Example 1
[0043] The preparation of the carbon-nitrogen-doped mesoporous silica support was the same as in Example 1.
[0044] Catalyst preparation
[0045] 0.33 g of copper acetate monohydrate was weighed and dissolved in an appropriate amount of deionized water to obtain a clear solution. A carbon-nitrogen-doped mesoporous silica support was added, and the mixture was stirred at 30 °C for 10 h. The water was removed by rotary evaporation, and the solid product was then placed in a vacuum oven at 70 °C for 10 h and calcined at 400 °C under a nitrogen atmosphere for 2 h to obtain the catalyst.
[0046] Catalyst evaluation
[0047] The catalyst evaluation method is the same as in Example 1, and the performance evaluation results of the catalyst are shown in Table 1.
[0048] Comparative Example 2
[0049] The preparation of the carbon-nitrogen-doped mesoporous silica support was the same as in Example 1.
[0050] Catalyst preparation
[0051] 0.41 g of copper sulfate pentahydrate was dissolved in an appropriate amount of deionized water to obtain a clear solution. A carbon-nitrogen-doped mesoporous silica support was added, and the mixture was stirred at 30 °C for 10 h. The water was removed by rotary evaporation. The solid product was then placed in a vacuum oven at 70 °C and dried for 10 h. Finally, it was calcined at 400 °C under a nitrogen atmosphere for 2 h to obtain the catalyst.
[0052] Catalyst evaluation
[0053] The catalyst evaluation method is the same as in Example 1, and the performance evaluation results of the catalyst are shown in Table 1.
[0054] Comparative Example 3
[0055] The preparation of the carbon-nitrogen-doped mesoporous silica support was the same as in Example 1.
[0056] Catalyst preparation
[0057] 0.25 g of copper chloride dihydrate was dissolved in an appropriate amount of deionized water to obtain a clear solution. A carbon-nitrogen-doped mesoporous silica support was added, and the mixture was stirred at 30 °C for 10 h. The water was removed by rotary evaporation. The solid product was then placed in a vacuum oven at 70 °C and dried for 10 h. Finally, it was calcined at 400 °C under a nitrogen atmosphere for 2 h to obtain the catalyst.
[0058] Catalyst evaluation
[0059] The catalyst evaluation method was the same as in Example 1, and the performance evaluation results of the catalyst are shown in Table 1. It can be seen that using copper nitrate trihydrate as a copper salt precursor yields the best catalytic performance.
[0060] copper salt precursor DMO conversion rate (%) EG selectivity (%) Example 1 Copper nitrate trihydrate 100 98.5 Comparative Example 1 Copper acetate monohydrate 93.9 78.4 Comparative Example 2 Copper sulfate pentahydrate 82.7 67.9 Comparative Example 3 Copper chloride dihydrate 73.2 59.3
[0061] Table 1: Performance evaluation of catalysts prepared from different copper salt precursors
[0062] Example 2
[0063] The preparation of mesoporous silica material is the same as in Example 1.
[0064] Preparation of carbon and nitrogen-doped mesoporous silica supports:
[0065] 1g of mesoporous silica was added to 100mL of deionized water, sonicated for 10min, and then 0.4g of urea was added. The mixture was stirred at 30℃ for 20h, and the water was removed by rotary evaporation. The solid product was then placed in a vacuum oven at 70℃ for 10h and calcined at 550℃ under a nitrogen atmosphere for 2h to obtain a carbon-nitrogen-doped mesoporous silica support.
[0066] The catalyst was prepared in the same manner as in Example 1.
[0067] Catalyst evaluation
[0068] The catalyst evaluation method is the same as in Example 1, and the performance evaluation results of the catalyst are shown in Table 2.
[0069] Example 3
[0070] The preparation of mesoporous silica material is the same as in Example 1.
[0071] Preparation of carbon and nitrogen-doped mesoporous silica supports:
[0072] 1g of mesoporous silica was added to 100mL of deionized water, sonicated for 10min, and then 1.2g of urea was added. The mixture was stirred at 30℃ for 20h, and the water was removed by rotary evaporation. The solid product was then placed in a vacuum oven at 70℃ for 10h and calcined at 550℃ under a nitrogen atmosphere for 2h to obtain a carbon-nitrogen-doped mesoporous silica support.
[0073] The catalyst was prepared in the same manner as in Example 1.
[0074] Catalyst evaluation
[0075] The catalyst evaluation method is the same as in Example 1, and the performance evaluation results of the catalyst are shown in Table 2.
[0076] Comparative Example 4
[0077] The preparation of mesoporous silica material is the same as in Example 1.
[0078] Catalyst preparation
[0079] Weigh 0.4g of copper nitrate trihydrate and dissolve it in an appropriate amount of deionized water to obtain a clear solution. Add mesoporous silica material and stir at 30℃ for 10h. Remove the water by rotary evaporation. Then place the solid product in a vacuum oven at 70℃ and dry for 10h. Calcine it at 400℃ under a nitrogen atmosphere for 2h to obtain the catalyst.
[0080] Catalyst evaluation
[0081] The catalyst evaluation method is the same as in Example 1, and the performance evaluation results of the catalyst are shown in Table 2.
[0082] Comparative Example 5
[0083] The preparation of mesoporous silica material is the same as in Example 1.
[0084] Preparation of carbon and nitrogen-doped mesoporous silica supports:
[0085] 1g of mesoporous silica was added to 100mL of deionized water, sonicated for 10min, and then 0.8g of melamine was added. The mixture was stirred at 30℃ for 20h, and the water was removed by rotary evaporation. The solid product was then placed in a vacuum oven at 70℃ for 10h and calcined at 550℃ under a nitrogen atmosphere for 2h to obtain a carbon-nitrogen-doped mesoporous silica support.
[0086] The catalyst was prepared in the same manner as in Example 1.
[0087] Catalyst evaluation
[0088] The catalyst evaluation method is the same as in Example 1, and the performance evaluation results of the catalyst are shown in Table 2.
[0089] Comparative Example 6
[0090] The preparation of mesoporous silica material is the same as in Example 1.
[0091] Preparation of carbon and nitrogen-doped mesoporous silica supports:
[0092] 1g of mesoporous silica was added to 100mL of deionized water and sonicated for 10min. Then, 0.8g of melamine was added and stirred at 30℃ for 20h. The water was removed by rotary evaporation. The solid product was then placed in a vacuum oven at 70℃ and dried for 10h. Finally, it was calcined at 550℃ under a nitrogen atmosphere for 2h to obtain a carbon-nitrogen-doped mesoporous silica support.
[0093] The catalyst was prepared in the same manner as in Example 1.
[0094] Catalyst evaluation
[0095] The catalyst evaluation method is the same as in Example 1, and the performance evaluation results of the catalyst are shown in Table 2.
[0096]
[0097] Table 2: Performance evaluation of catalysts prepared with different types and amounts of carbon and nitrogen precursors.
[0098] As shown in Table 2, compared with the sample without carbon and nitrogen doping (Comparative Example 4), catalysts prepared by doping with different types of carbon and nitrogen precursors (Examples 2, 3, Comparative Examples 5 and 6) all showed improved catalytic performance in the hydrogenation reaction of oxalate ester. Furthermore, catalysts prepared by doping with an appropriate amount of urea as a carbon and nitrogen precursor exhibited the best catalytic performance (Example 1).
[0099] The copper-based catalysts supported on carbon and nitrogen-doped mesoporous silica in Comparative Example 4, Example 1, Example 2, and Example 3 of this invention were characterized using thermogravimetric analysis. Figure 1 As can be seen, compared with the sample without carbon and nitrogen doping (comparative sample 4), the actual weight loss of Examples 1-3 was 3.4 wt.%, 1.6 wt.%, and 5.6 wt.%, respectively, indicating that the present invention can flexibly control the carbon and nitrogen content by adjusting the amount of urea precursor.
[0100] The copper-based catalysts supported on carbon and nitrogen-doped mesoporous silica in Comparative Example 4, Example 1, Example 2, and Example 3 were characterized using nitrogen isothermal physisorption. Figure 2 It can be seen that, compared with mesoporous silica, the volume of the nitrogen adsorption-desorption hysteresis loop in the catalyst loaded with copper (Comparative Sample 4) is significantly reduced and the average pore size is also reduced. For carbon and nitrogen doped mesoporous silica after loading with copper (Examples 1-3), the volume and average pore size of its hysteresis loop are similar to those of the undoped mesoporous silica catalyst loaded with copper (Comparative Sample 4), indicating that the carbon and nitrogen content is low and has almost no effect on the pores of the catalyst.
[0101] The particle size of the reduced catalyst was characterized using X-ray diffraction (XRD) patterns. Figure 3It can be found that the catalyst without carbon and nitrogen doping (comparative sample 4) shows a sharp characteristic peak at 2θ of 43.5° after reduction, which belongs to the Cu(111) crystal plane (JCPDS 04-0836). The copper particle size is calculated to be about 8.5 nm using the Scherrer formula. However, the characteristic peak intensity at 2θ of 43.5° of the catalyst with carbon and nitrogen doping is significantly weakened after reduction, indicating that the copper particle size has decreased (Examples 1-3).
[0102] The morphology and particle size of the catalyst were analyzed using transmission electron microscopy (TEM) images and corresponding particle size distribution charts, such as... Figure 4 As shown, the catalyst supports all have obvious mesopore sizes, and the copper particle size of the catalyst without carbon and nitrogen doping (comparative sample 4) after reduction is about 10.0 nm, while the copper particle size of the carbon and nitrogen doped catalyst of the present invention (Example 1) after reduction is about 4.2 nm.
[0103] The above results indicate that nitrogen species in carbon-nitrogen doping can coordinate with copper species, anchoring them and inhibiting copper particle growth. To demonstrate the presence of nitrogen species and their coordination with copper, X-ray photoelectron spectroscopy (XPS) was used for characterization. Figure 5 It can be observed that the energy spectrum of the catalyst without carbon and nitrogen doping (comparative sample 4) does not contain nitrogen element, nor does it contain Cu-N coordinated species. However, the energy spectrum of the carbon and nitrogen doped catalyst of this invention (Example 1) shows a nitrogen element signal peak. The weak signal may be due to the low nitrogen content. At the same time, Cu-N coordinated species information was clearly detected, proving that the nitrogen species in the carbon and nitrogen support can coordinate with copper, have an anchoring effect on copper species, and inhibit the growth of copper particles.
[0104] exist Figure 5 As can be seen from the Cu 2p spectrum, in the Cu-N species formed on the carbon-nitrogen-doped catalyst (Example 1), the binding energy of the Cu species is higher than that of the Cu species. 0 or Cu + The species, while the catalyst without carbon and nitrogen doping (comparative sample 4) contains only Cu. 0 or Cu + The presence of different nitrogen species indicates that the Cu-N species formed by carbon and nitrogen doping leads to a more electron-deficient state for the active copper species. Further identification of different nitrogen species was achieved through X-ray photoelectron spectroscopy (XPS) characterization of nitrogen. Figure 6 As can be seen, the nitrogen element in the carbon-nitrogen-doped catalysts (Example 1, Example 2) includes graphitic nitrogen species and pyrrole nitrogen species. In Example 1, the content of pyrrole nitrogen species is higher than that of graphitic nitrogen species, while in Example 2, the content of graphitic nitrogen species is higher than that of pyrrole nitrogen species. However, according to... Figure 3The X-ray diffraction (XRD) patterns in Example 1 show that the characteristic peak intensity of metallic copper at 2θ of 43.5° is significantly weaker than that in Example 2, and the catalytic activity of Example 2 is significantly lower than that of Example 1. This indicates that the coordination of pyrrole nitrogen species with copper species achieves the anchoring and high dispersion of copper species.
[0105] Oxalate hydrogenation is a continuous series reaction. Oxalate first hydrogenates to methyl glycolate (MG), which then hydrogenates to ethylene glycol, indicating that the degree of methyl glycolate adsorption significantly affects the activity for ethylene glycol formation. To further investigate the mechanism of carbon-nitrogen doping in oxalate hydrogenation, the desorption intensity of methyl glycolate was tested on both a non-carbon-nitrogen-doped catalyst (Comparative Sample 4) and a carbon-nitrogen-doped catalyst (Example 1), and the signal was detected using mass spectrometry (MG-TPD-MS). The results are as follows: Figure 7 As shown, methyl glycolate desorbs at around 160°C on the carbon-nitrogen-doped catalyst (Comparative Sample 4), while it desorbs at a higher temperature of around 175°C on the carbon-nitrogen-doped catalyst (Example 1). This indicates that the carbon-nitrogen-doped catalyst (Example 1) has a stronger adsorption and activation strength for methyl glycolate, and therefore it is easier to generate ethylene glycol at low temperature and low pressure.
[0106] Examples 4-5
[0107] The catalyst preparation method is the same as in Example 1.
[0108] The catalyst evaluation method was the same as in Example 1, except that the reaction pressure was changed and everything else remained the same. The performance evaluation results of the catalyst are shown in Table 3.
[0109] Examples 6-8
[0110] The catalyst preparation method is the same as in Example 1.
[0111] The catalyst evaluation method was the same as in Example 1, except that the liquid hourly space velocity (LHSV) was changed, while other parameters remained the same. The performance evaluation results of the catalyst are shown in Table 3.
[0112] Examples 9-11
[0113] The catalyst preparation method is the same as in Example 1.
[0114] The catalyst evaluation method was the same as in Example 1, except that the reaction temperature was changed. The performance evaluation results of the catalyst are shown in Table 3.
[0115] Examples 12-14
[0116] The catalyst preparation method is the same as in Example 1.
[0117] The catalyst evaluation method was the same as in Example 1, except that the hydrogen-ester ratio was changed, while other parameters remained the same. The performance evaluation results of the catalyst are shown in Table 3.
[0118] Examples 15-17
[0119] The catalyst preparation method is the same as in Example 1.
[0120] The catalyst evaluation method was the same as in Example 11, except that the liquid hourly space velocity (LHSV) and pressure were changed, while other parameters remained the same. The performance evaluation results of the catalyst are shown in Table 3.
[0121]
[0122]
[0123] Table 3: Catalyst performance evaluation under different conditions
[0124] Examples 4-17 show that the reaction was successful at a pressure of 0.5 MPa, a hydrogen-to-ester ratio of 100, and a liquid hourly space velocity of 0.2 h⁻¹. -1 At a reaction temperature of 170℃, better DMO conversion and EG selectivity were observed. Simultaneously, at a high temperature of 190℃, a reaction pressure of 2.5 MPa, a hydrogen-to-ester ratio of 100, and a liquid hourly space velocity of 1.2 h⁻¹, further improvements were achieved. -1 Even at that time, it still exhibits excellent DMO conversion rate and EG selectivity.
Claims
1. The application of a copper-based catalyst supported on carbon and nitrogen-doped mesoporous silica in the hydrogenation of oxalate to ethylene glycol, characterized in that: The catalyst comprises copper, carbon, nitrogen, and silicon oxide, wherein copper accounts for 5-15 wt.% of the catalyst mass, carbon accounts for 0.5-5 wt.% of the catalyst mass, nitrogen accounts for 0.5-2 wt.% of the catalyst mass, and silicon oxide accounts for 78-94 wt.% of the catalyst mass; the copper species in the catalyst coordinates with pyrrole nitrogen to form Cu-N species; The catalyst has a specific surface area of 450-500 m². 2 / g, with an average pore volume of 0.7-1.0 cm³. 3 / g, with an average pore size of 5.5-6.0nm; The method for preparing the catalyst includes the following steps: The template agent was completely dissolved in an acidic aqueous solution, a silicon source was added, and hydrothermal crystallization was carried out in a sealed container. The product after hydrothermal crystallization was washed, dried, and calcined to obtain mesoporous silica. Carbon-nitrogen precursors were dissolved in water, mesoporous silica was added, and carbon-nitrogen-doped mesoporous silica support was obtained after drying and calcination. A copper salt precursor was dissolved in deionized water, and a carbon-nitrogen-doped mesoporous silica support was added. After drying and calcination, a copper-based catalyst supported on carbon-nitrogen-doped mesoporous silica was obtained. The carbon-nitrogen precursor is any one of urea, melamine, and dimelamine; the copper salt precursor is any one of copper acetate, copper sulfate, copper chloride, and copper nitrate; the template agent is polyethylene oxide-polypropylene oxide-polyethylene oxide; the mass ratio of the carbon-nitrogen precursor to mesoporous silica is 0.5-1.
0. The catalyst is used in the hydrogenation of oxalate to ethylene glycol. It utilizes the electronic effects of Cu-N species to promote the adsorption and activation of reactants, thereby achieving efficient hydrogenation of oxalate to ethylene glycol under low temperature and low pressure. In the hydrogenation of oxalate to ethylene glycol, the reaction pressure is 0.1-1.5 MPa, the reaction temperature is 160-190℃, the hydrogen-to-ester ratio is 60-120, and the liquid hourly mass hourly space velocity (LIHSV) is 0.05-0.3 h⁻¹, where LIHSV refers to the mass hourly space velocity of oxalate.
